Touch Me Please—When This Enhanced Community Quarantine is Over: Sexual Intimacies Among Pre-Marital Partners During Pandemic-Induced Lockdown - Collado, Zaldy C (Archīum Ateneo, 2021)
The study aims to examine the experiences of pre-marital; noncohabiting partners while coping with the Covid-19-induced lockdown. With specific focus on sexual intimacies; our interest is to investigate the degree or extent by which the pandemic has constrained people’s sexual interests and expressions with the intention to determine whether or not the overall relationship would be negatively affected by the paucity of sexual encounters. Findings drawn from online interviews involving 28 participants reveal that the pandemic has indeed affected sexual intimacy aspirations among partners; with some participants calling these times as “dry season.” For this very reason; the pandemic has also emerged as a sexual issue. Further results reveal that partners employ technology-based strategies in order to satisfy their sexual desires during these times when restrictions in movement are in place. Trust; love; communication and understanding serve also to assure partners of the integrity of the relationship. The study suggests that the loss of physical sexual encounters during lockdowns is not sufficient to result in negative relationship outcomes.